THE EFFECT OF STUDENT-CENTRED APPROACH VS. TEACHER CENTERED TEACHING ON KURDISH EFL UNIVERSITY LEARNERS’ PERFORMANCE IN ENGLISH GRAMMAR - Findo, Hussein Asaad; ali ahmed, Hussein (Journal of Duhok University, 2023)
The popularity of the student-centred learning approach that focuses on the learner as the main element in the teaching-learning process highlights a noticeable shift from the teacher-centred teaching where a teacher is viewed to be the only element that is operating such a system. On this basis, The current research attends to the investigation of the effect of the student-centered approach  on Kurdish EFL university students' performance in English grammar. It is hypothesized that the student-centred approach positively affects performance in English grammar at university level. To bring about this objective, and validate the already stated hypothesis, 66 3rd year Kurdish EFL students were randomly chosen from among the students at  the Department of English, College of Basic Education in Amedi, University of  Duhok, Kurdistan Region. The selected sample of the students was divided into two  groups: experimental and control. Both groups were subjected to a pre-test that comprised certain topics of English grammar and showed almost identical levels of performance. That was followed by carrying out the experiment of teaching the experimental group according to the student-centered approach, and the control group  on the basis of the traditional method of teaching, i.e. teacher-centered approach. On the completion of the experiment, the two groups were retested by a post-test. On scoring the two groups’ performance on the post-test, and applying the independent samples t-test and the SPSS for inferential statistics, it was found out that the student-centered approach had positively contributed to Kurdish EFL university learners’ performance in English grammar compared to the teacher centered approach. Such a positive effect of the student-centred approach evidenced the importance of applying it by teachers of subjects other than English grammar at university level